Overexpression of PSAT1 promotes metastasis of lung adenocarcinoma by suppressing the IRF1-IFNγ axis - Chan, Yung-Chieh; Chang, Yu-Chan; Chuang, Hsiang-Hao; Yang, Yi-Chieh; Lin, Yuan-Feng; Huang, Ming-Shyan; Hsiao, Michael; Yang, Chih-Jen; Hua, Kuo-Tai (Oncogene, 2020)
An increasing number of enzymes involved in serine biosynthesis have been identified and correlated with malignant evolution in various types of cancer. Here we showed that the overexpression of phosphoserine aminotransferase 1 (PSAT1) is widely found in lung cancer tissues compared with nontumor tissues and predicts a poorer prognosis in patients with lung adenocarcinoma. PSAT1 expression was examined in a tissue microarray by immunohistochemistry. The data show that the knockdown of PSAT1 dramatically inhibits the in vitro and in vivo metastatic potential of highly metastatic lung cancer cells; conversely, the enforced expression of exogenous PSAT1 predominantly enhances the metastatic potential of lung cancer cells. Importantly, manipulating PSAT1 expression regulates the in vivo tumor metastatic abilities in lung cancer cells. Adjusting the glucose and glutamine concentrations did not alter the PSAT1-driven cell invasion properties, indicating that this process might not rely on the activation of its enzymatic function. RNA microarray analysis of transcriptional profiling from PSAT1 alternation in CL1-5 and CL1-0 cells demonstrated that interferon regulatory factor 1 (IRF1) acts as a crucial regulator of PSAT1-induced gene expression upon metastatic progression. Decreasing the IRF1-IFIH1 axis compromised the PSAT1-prompted transcriptional reprogramming in cancer cells. Our results identify PSAT1 as a key regulator by a novel PSAT1/IRF1 axis in lung cancer progression, which may serve as a potential biomarker and therapeutic target for the treatment of lung cancer patients.